2018
DOI: 10.1080/10826068.2018.1479862
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of palladium nanoparticles using Diospyros kaki leaf extract and determination of antibacterial efficacy

Abstract: Palladium, the building block of white gold, has been found to exhibit extraordinary properties in nanotechnological products produced in recent years. The most prominent feature of palladium is adsorbing and storing high levels of hydrogen. Therefore, the demand for palladium in the world increased excessively in the 2000s. In the present study, palladium nanoparticles (PdNPs) were biosynthesized by the extract of Diospyros kaki leaves as bio-stimulator. D. kaki, also called persimmon, was collected in a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…b) exhibits characteristic FTIR peaks at 3466, 3010, 2971, 1715.53, 1424.33, 1357.03, 1220.84, 1092.54, 895.57, 793.91, and 529.54 cm −1 attributed to the stretching of O-H, C-H (aromatic), C-H (aliphatic), C � O, C � C, N-O in NO 3 , C-N of primary amine, and C-X (halogen), respectively[25]. e phenolic compounds in the leaf extract of D. kaki are responsible for the reduction of precursor's salt and capping of the metal cation, as shown in Figure2[26].…”
mentioning
confidence: 99%
“…b) exhibits characteristic FTIR peaks at 3466, 3010, 2971, 1715.53, 1424.33, 1357.03, 1220.84, 1092.54, 895.57, 793.91, and 529.54 cm −1 attributed to the stretching of O-H, C-H (aromatic), C-H (aliphatic), C � O, C � C, N-O in NO 3 , C-N of primary amine, and C-X (halogen), respectively[25]. e phenolic compounds in the leaf extract of D. kaki are responsible for the reduction of precursor's salt and capping of the metal cation, as shown in Figure2[26].…”
mentioning
confidence: 99%
“…The antibacterial property of PdNPs was recently discovered and the reported data showed that PdNPs have a high potential for antimicrobial applications [31,33,46,47,[78][79][80]. As illustrated in Figure 1, the antibacterial mechanism of PdNPs included both physical and chemical modes.…”
Section: Palladium Nanoparticles For Antibacterial Therapymentioning
confidence: 96%
“…They were applied for antioxidant, antibacterial, and antiproliferative activates on the human leukemia cell line [31]. PdNPs, which were synthesized by Diospyros kaki leaves, were in sizes ranging from 50 to 120 nm and showed strong antibacterial efficacy on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) [46]. Porous PdNPs with rough protuberances were prepared a chaga mushroom (Inonotus obliquus) extract [27].…”
Section: Synthesismentioning
confidence: 99%
“…These phytochemicals are absorbed onto the surface of the nanostructures through π -electron interactions if other strong ligating agents are not present [ 100 , 103 , 104 ]. Once again, agglomeration was an issue faced by researchers, deeming the particles thermodynamically unstable as they are, by nature, finely divided mass [ 105 , 106 ].…”
Section: Green Synthesis Of Transitional Metals and Their Oxidesmentioning
confidence: 99%
“…These phytochemicals are absorbed onto the surface of the nanostructures through π-electron interactions if other strong ligating agents are not present [100,103,104]. Moreover, agglomeration was another issue faced by researchers, deeming them thermodynamically unstable as they are, by nature, finely divided mass [105,106]. Moreover, Sharmila et al (2017) conducted experiments that resulted in the successful synthesis of palladium nanoparticles by utilizing the aqueous leaf extract of Filicium decipiens.…”
Section: Palladium and Palladium Oxide Nanoparticlesmentioning
confidence: 99%